Drug targets and biomarker identification from computational study of human notch signaling pathway - Chowdhury, Saikat; Sarkar, Ram Rup (Clinical and Experimental Pharmacology and Physiology, 2013)
Notch signaling pathway is widely implicated in controlling various cellular functions, cell fate determination, and stem cell renewal in human but aberrant activity in cancer stem cells may cause different types of cancers. Understanding the complexity of this pathway to identify important targets for cancer therapy and to suppress the pathway activity without affecting the normal functions is of utmost importance to clinical and experimental pharmacologists. For developing therapeutic strategy, non availability of detailed molecular interactions, complex regulations and cross talks with other pathways pose a serious challenge to get a coherent understanding of this pathway. This motivated us to reconstruct the largest human cell specific Notch pathway with more number of molecules and interactions available from literatures and databases. To identify probable drug targets and biomarkers for cancer prognosis, we also performed computational study of the pathway using structural and logical analysis and identified important hub proteins, cross talks and feedback mechanisms. The model simulation is validated using reported mRNA expression profile in Glioblastoma cell line and the predictions not only show significant accuracy but also able to identify the undetermined expressions. From our simulation, to identify novel combinations of drug targetable proteins and better substitute for GAMMA SECRETASE inhibition, we proposed two alternative scenarios: partial suppression of Notch target proteins by NICD1 & HIF1A; and complete suppression by NICD1 & MAML, in Glioblastoma cell line. This reconstructed Notch signaling pathway and the computational analysis for identifying new biomarkers and combinatory drug targets will be useful for future in-vitro and in-vivo analysis to control different cancers

Structural and logical analysis of a comprehensive hedgehog signaling pathway to identify alternative drug targets for glioma, colon and pancreatic cancer - Chowdhury, Saikat; Pradhan, Rachana N.; Sarkar, Ram Rup (Plos One, 2013)
Hedgehog is an evolutionarily conserved developmental pathway, widely implicated in controlling various cellular responses such as cellular proliferation and stem cell renewal in human and other organisms, through external stimuli. Aberrant activation of this pathway in human adult stem cell line may cause different types of cancers. Hence, targeting this pathway in cancer therapy has become indispensable, but the non availability of detailed molecular interactions, complex regulations by extra- and intra-cellular proteins and cross talks with other pathways pose a serious challenge to get a coherent understanding of this signaling pathway for making therapeutic strategy. This motivated us to perform a computational study of the pathway and to identify probable drug targets. In this work, from available databases and literature, we reconstructed a complete hedgehog pathway which reports the largest number of molecules and interactions to date. Using recently developed computational techniques, we further performed structural and logical analysis of this pathway. In structural analysis, the connectivity and centrality parameters were calculated to identify the important proteins from the network. To capture the regulations of the molecules, we developed a master Boolean model of all the interactions between the proteins and created different cancer scenarios, such as Glioma, Colon and Pancreatic. We performed perturbation analysis on these cancer conditions to identify the important and minimal combinations of proteins that can be used as drug targets. From our study we observed the under expressions of various oncoproteins in Hedgehog pathway while perturbing at a time the combinations of the proteins GLI1, GLI2 and SMO in Glioma; SMO, HFU, ULK3 and RAS in Colon cancer; SMO, HFU, ULK3, RAS and ERK12 in Pancreatic cancer. This reconstructed Hedgehog signaling pathway and the computational analysis for identifying new combinatory drug targets will be useful for future in-vitro and in-vivo analysis to control different cancers.

Comparison of human cell signaling pathway databases-evolution, drawbacks and challenges - Chowdhury, Saikat; Sarkar, Ram Rup (Database-the Journal of Biological Databases and Curation, 2015)
Elucidating the complexities of cell signaling pathways is of immense importance to gain understanding about various biological phenomenon, such as dynamics of gene/protein expression regulation, cell fate determination, embryogenesis and disease progression. The successful completion of human genome project has also helped experimental and theoretical biologists to analyze various important pathways. To advance this study, during the past two decades, systematic collections of pathway data from experimental studies have been compiled and distributed freely by several databases, which also integrate various computational tools for further analysis. Despite significant advancements, there exist several drawbacks and challenges, such as pathway data heterogeneity, annotation, regular update and automated image reconstructions, which motivated us to perform a thorough review on popular and actively functioning 24 cell signaling databases. Based on two major characteristics, pathway information and technical details, freely accessible data from commercial and academic databases are examined to understand their evolution and enrichment. This review not only helps to identify some novel and useful features, which are not yet included in any of the databases but also highlights their current limitations and subsequently propose the reasonable solutions for future database development, which could be useful to the whole scientific community.

Temporal protein expression pattern in intracellular signalling cascade during T-cell activation: a computational study - Ganguli, Piyali; Chowdhury, Saikat; Bhowmick, Rupa; Sarkar, Ram Rup (Journal of Biosciences, 2015)
Various T-cell co-receptor molecules and calcium channel CRAC play a pivotal role in the maintenance of cell's functional responses by regulating the production of effector molecules (mostly cytokines) that aids in immune clearance and also maintaining the cell in a functionally active state. Any defect in these co-receptor signalling pathways may lead to an altered expression pattern of the effector molecules. To study the propagation of such defects with time and their effect on the intracellular protein expression patterns, a comprehensive and largest pathway map of T-cell activation network is reconstructed manually. The entire pathway reactions are then translated using logical equations and simulated using the published time series microarray expression data as inputs. After validating the model, the effect of in silico knock down of co-receptor molecules on the expression patterns of their downstream proteins is studied and simultaneously the changes in the phenotypic behaviours of the T-cell population are predicted, which shows significant variations among the proteins expression and the signalling routes through which the response is propagated in the cytoplasm. This integrative computational approach serves as a valuable technique to study the changes in protein expression patterns and helps to predict variations in the cellular behaviour.
Keywords: Boolean model; co-receptors and CRAC channel; synchronous and asynchronous simulation; T-cell signalling pathway; temporal gene expression patterns

Structural insight of NICD-MAML interactions: virtual screening, docking and molecular dynamics study for the identification of potential inhibitor - Sinha, Noopur; Chowdhury, Saikat; Sarkar, Ram Rup (Letters in Drug Design & Discovery, 2016)
Activation of Notch signalling pathway is triggered by binding of NICD to transcription factor CSL and transcriptional co-activator MAML, which involves in various biological functions as well as progression of diseases. Recent prediction shows suppression of cancer causing genes of this pathway through inhibition of NICD-MAML interaction. Through virtual screening against ``NCI Diversity 3'' of Zinc database, we identified a potential inhibitor ``ZINC01690699'' (1-N,4-N-bis[3-(1H-benzimidazol-2-yl)phenyl]benzene-1,4-dicarboxamide; 1-N, 4-dicarboxamide) possessing highest binding affinity to block the two distinct Binding Sites of NICD to inhibit NICD-MAML interaction and also found the most imperative and essential Binding Site (Site I). Inhibition of this interaction caused by binding of ZINC01690699 is validated by protein-protein docking and the prolonged binding as well as stability of NICD-Inhibitor complex is supported by molecular dynamics simulation. The study not only identifies the best inhibitor but also proposes a potential drug for the treatment of cancers.
Keywords: free energy of binding; MAML; NICD; Notch signalling; potential inhibitor; ZINC01690699

Exploring notch pathway to elucidate phenotypic plasticity and intra-tumor heterogeneity in gliomas - Chowdhury, Saikat; Sarkar, Ram Rup (Scientific Reports, 2019)
The phenotypic plasticity and self-renewal of adult neural (aNSCs) and glioblastoma stem cells (GSCs) are both known to be governed by active Notch pathway. During development, GSCs can establish differential hierarchy to produce heterogeneous groups of tumor cells belong to different grades, which makes the tumor ecosystem more complex. However, the molecular events regulating these entire processes are unknown hitherto. In this work, based on the mechanistic regulations of Notch pathway activities, a novel computational framework is introduced to inspect the intra-cellular reactions behind the development of normal and tumorigenic cells from aNSCs and GSCs, respectively. The developmental dynamics of aNSCs/GSCs are successfully simulated and molecular activities regulating the phenotypic plasticity and self-renewal processes in normal and tumor cells are identified. A novel scoring parameter ``Activity Ratio'' score is introduced to find out driver molecules responsible for the phenotypic plasticity and development of different grades of tumor. A new quantitative method is also developed to predict the future risk of Glioblastoma tumor of an individual with appropriate grade by using the transcriptomics profile of that individual as input. Also, a novel technique is introduced to screen and rank the potential drug-targets for suppressing the growth and differentiation of tumor cells.

Molecular basis of drug resistance in smoothened receptor: an in silico study of protein resistivity and specificity - Sinha, Noopur; Chowdhury, Saikat; Sarkar, Ram Rup (Proteins-Structure Function and Bioinformatics, 2019)
Smoothened (SMO) antagonist Vismodegib effectively inhibits the Hedgehog pathway in proliferating cancer cells. In early stage of treatment, Vismodegib exhibited promising outcomes to regress the tumors cells, but ultimately relapsed due to the drug resistive mutations in SMO mostly occurring before (primary mutations G497W) or after (acquired mutations D473H/Y) anti-SMO therapy. This study investigates the unprecedented insights of structural and functional mechanism hindering the binding of Vismodegib with sensitive and resistant mutant variants of SMO (SMOMut). Along with the basic dynamic understanding of Vismodegib-SMO complexes, network propagation theory based on heat diffusion principles is first time applied here to identify the modules of residues influenced by the individual mutations. The allosteric modulation by GLY497 residue in Vismodegib bound SMO wild-type (SMOWT) conformation depicts the interconnections of intermediate residues of SMO with the atom of Vismodegib and identify two important motifs (E-X-P-L) and (Q-A-N-V-T-I-G) mediating this allosteric regulation. In this study a novel computational framework based on the heat diffusion principle is also developed, which identify significant residues of allosteric site causing drug resistivity in SMOMut. This framework could also be useful for assessing the potential allosteric sites of different other proteins. Moreover, previously reported novel inhibitor ``ZINC12368305,'' which is proven to make an energetically favorable complex with SMOWT is chosen as a control sample to assess the impact of receptor mutation on its binding and subsequently identify the important factors that govern binding disparity between Vismodegib and ZINC12368305 bound SMOWT/Mut conformations.
Keywords: allosteric sites; molecular dynamics simulation; Mutation; smoothened receptor; Vismodegib